Talent concentration and competitive imbalance in European soccer - Frick, Bernd; Quansah, Tommy Kweku; Lang, Markus (Frontiers in Sports and Active Living, 2023)
Introduction: While most of the available literature on competitive balance analyses its impact on ticket sales and TV audiences, less empirical research is available that examines the observable variation in competitive balance across leagues and over time. This paper studies the concentration of player talent and end-of-season league points to empirically assess whether leagues with a more equal distribution of player talent produce a more balanced competition than leagues with less equal distribution. Methods: The longitudinal data we use to estimate our empirical model comes from professional soccer leagues in twelve Western European countries from 2005/06 thru 2020/21, yielding 5,299 club-season observations. Results: Our empirical analysis indicates that talent concentration in a league significantly and positively impacts points concentration in that league. However, in specifications controlling for year, country, and division, this impact is only weakly significant or insignificant, suggesting that talent concentration does not significantly affect competitive balance in that league. Additionally, our findings demonstrate that the relationship between talent and points concentration does not vary considerably across the European leagues or over time. Discussion: Our results suggest that repeated participation in the UEFA Champions League (UCL), with its considerable monetary returns by (more or less) the same subset of teams, does not increase competitive imbalance in the respective national league. Thus, with relatively few additional regulatory interventions, the promotion and relegation system in the open European soccer leagues seems effective in ensuring a balanced competition.